2022
DOI: 10.7759/cureus.24878
|View full text |Cite
|
Sign up to set email alerts
|

‏Impact of Food Habit on Cataracts Development Among Adults in Aseer Region, Saudi Arabia: A Retrospective Study

Abstract: Background: Cataracts are the main cause of visual impairment among the aging population, with a high impact on patients’ quality of life. It has been suggested that the antioxidant carotenoids lutein and zeaxanthin may play a role in cataract prevention. Recently, significant evidence has associated abnormal glucose metabolism with an increased likelihood of the development of cataracts. Aim: The current study aims to assess the relationship between nutrition and cataracts among adults in the Aseer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…their results were in line with data from Lew et al [ 176 ] and Sanz-González et al [ 174 ]. Zeaxanthin may also slow down the rate of cataractogenesis [ 177 , 178 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…their results were in line with data from Lew et al [ 176 ] and Sanz-González et al [ 174 ]. Zeaxanthin may also slow down the rate of cataractogenesis [ 177 , 178 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lutein also acts via antioxidative and barrier properties to protect the retina photoreceptors, as seen in the work of Obana et al [ 193 ]. It has been shown to reduce the risk of age-related macular degeneration, glaucoma, cataracts, and other eye diseases [ 178 , 194 , 195 ]. A systematic review concluded that lutein-supplemented eyes performed better due to their neuroprotective properties and preservation of synaptic activity [ 176 ].…”
Section: Resultsmentioning
confidence: 99%